We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**0 **

The common difference is -x/2. Therefore we have the sequence continue as:

2x, 3x/2, x, x/2, 0, -x/2, -x, -3x/2, -2x, -5x/2......etc.

And -5x/2 being the 10th term.

Guest Jun 26, 2017

#2**0 **

We have:

-5x/2 = 2x + (N - 1)* -x/2

Solve for N:

-(5 x)/2 = 2 x - 1/2 x (N - 1)

-(5 x)/2 = 2 x - 1/2 (N - 1) x is equivalent to 2 x - 1/2 (N - 1) x = -(5 x)/2:

2 x - 1/2 x (N - 1) = -(5 x)/2

Expand out terms of the left hand side:

(5 x)/2 - (N x)/2 = -(5 x)/2

Subtract (5 x)/2 from both sides:

-(N x)/2 = -5 x

Divide both sides by -x/2:

**Answer: | N = 10 which is the 10th term of your sequence.**

Guest Jun 26, 2017